Surveillance on the attitude to the postgraduate degree in the graduates of Jichi Medical University - KUMADA, Maki; KAMESAKI, Toyomi; IWAHANA, Hiroyuki (Igaku Kyoiku / Medical Education (Japan), 2007)
1) Surveillance on the attitude to the postgraduate degree was performed by a questionnaire in the graduates of Jichi Medical University, who were engaged in community medicine soon after graduating and had not so many opportunities to conduct medical research. 2) More than a half of the respondents had obtained the postgraduate degree after the 9-year mandatory period of engagement as clinical physicians in the local communities.Among the respondents not having the postgraduate degree, 50-60% of them felt the need for the degree. 3) The remarks of the degree holders indicated that objective assessment ability and the scientific point of view acquired in the degree process had favorable effects on their performance as clinicians thereafter. The result suggested that the substantialization of research in the field of clinical medicine was demanded in the graduate school.